2003
DOI: 10.1073/pnas.0931464100
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of barley BAX inhibitor 1 induces breakdown of mlo -mediated penetration resistance to Blumeria graminis

Abstract: Cell death regulation is linked to pathogen defense in plants and animals. Execution of apoptosis as one type of programmed cell death in animals is irreversibly triggered by cytochrome c release from mitochondria via pores formed by BAX proteins. This type of programmed cell death can be prevented by expression of BAX inhibitor 1 (BI-1), a membrane protein that protects cells from the effects of BAX by an unknown mechanism. In barley, a homologue of the mammalian BI-1 is expressed in response to inoculation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
138
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 41 publications
3
138
0
4
Order By: Relevance
“…mlo-mediated resistance during papillae formation is extremely effective, although in the rare case when penetration does occur, Bgh colonization of the leaf tissue proceeds normally (Jørgensen, 1994). Similarly, overexpression of the barley homolog of BI-1 in epidermal cells generates supersusceptibility (Hü ckelhoven et al, 2003). BI-1 was found to negatively regulate the penetration resistance mediated by mlo and almost restored the penetration efficiency (PE) of Bgh to wild-type levels (Hü ckelhoven et al, 2003).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…mlo-mediated resistance during papillae formation is extremely effective, although in the rare case when penetration does occur, Bgh colonization of the leaf tissue proceeds normally (Jørgensen, 1994). Similarly, overexpression of the barley homolog of BI-1 in epidermal cells generates supersusceptibility (Hü ckelhoven et al, 2003). BI-1 was found to negatively regulate the penetration resistance mediated by mlo and almost restored the penetration efficiency (PE) of Bgh to wild-type levels (Hü ckelhoven et al, 2003).…”
mentioning
confidence: 99%
“…Edr1, AtWRKY58, HvWRKY1/2, and BAX inhibitor-1 (BI-1) are examples of well-characterized negative regulators in the known signal and transcriptional activation cascades. By contrast, genes such as the Mlo negative regulator of penetration resistance and several lesion-mimic mutants, such as lsd1, have only recently been characterized with regard to regulatory roles and importance during defense (Bü schges et al, 1997;Frye et al, 2001;Hü ckelhoven et al, 2003;Wang et al, 2006;Shen et al, 2007). Although the former group of genes direct our attention to the complexity and redundancy of the regulatory network of plant defense, the latter set of genes are expanding our understanding of nonhost resistance, biotrophy, and the formation and/or progression of necrosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Kim et al 44,45 reported that binding of barley MLO to CaM (HvCaM3) is required for this Mlo-mediated defense response. Interestingly, Hü ckelhoven et al 15 found that barley BI-1 overexpression resulted in breakdown of the penetration resistance to B. graminis in the barley mlo mutant, suggesting that BI-1 and Mlo may have similar functions in plant defense responses. The observation that Mlo binds to HvCaM3 led Ihara-Ohori et al 46 to study CaM-binding ability of AtBI-1.…”
Section: Molecular Analysis Of Atbi-1-interacting Factorsmentioning
confidence: 99%
“…and their expression levels are usually enhanced during aging (senescence) and under stress conditions, suggesting that BI-1 function is physiologically associated with cell death control and/or stress management. [12][13][14][15][16][17][18][19][20] In fact, numerous studies by transgenic approaches have revealed that overexpression of plant BI-1 resulted in attenuation of cell death induced by biotic stresses (pathogens) and abiotic stresses such as heat, cold, drought, salt and chemical-induced oxidative stresses, which induce massive accumulation of ROS before cell death activation. [16][17][18][19][20] Interestingly, it was shown that elevated intracellular ROS levels by Bax expression was not abrogated in AtBI-1 (Arabidopsis BI-1) overexpressing Arabidopsis plants, although plant cell death was strongly attenuated.…”
Section: Bi-1 Is a Broad-spectrum Cell Death Suppressor In Plantsmentioning
confidence: 99%